INTEGRASI TOTAL QUALITY MANAGEMENT DAN PERFORMANCE MANAGEMENT SYSTEM UNTUK MENINGKATKAN KINERJA KARYAWAN DI PERUSAHAAN MANUFAKTUR - Putra, Arif Rachman; Darmawan, Didit (Universitas Mahendradatta Denpasar, 2025)
This study explores the effect of Total Quality Management (TQM) and Performance Management System (PMS) on employee performance in manufacturing companies. This study uses a quantitative approach with data collection through questionnaires. Results show that TQM and PMS have a significant influence on improving employee performance, with PMS making a more dominant contribution. TQM plays a role through continuous improvement approaches and employee participation, while PMS supports through results-based evaluation, goal clarity, and feedback. This research provides recommendations for integrating TQM and PMS in management strategies to support sustainable employee performance improvement.